Development of a Pediatric Goal-Centered Upper Limb Spasticity Home Exercise Therapy Program for Use in a Phase-III Trial of Abobotulinumtoxina (Dysport®). (4th March 2019) - Shierk, Angela; Jiménez-Moreno, A. Cecilia; Roberts, Heather; Ackerman-Laufer, Shirley; Backer, Gretchen; Bard-Pondarre, Rachel; Cekmece, Cigdem; Pyrzanowska, Weronika; Vilain, Claire; Delgado, Mauricio R.
Abstract: Aims: To create a standardized home exercise therapy program that could be implemented by international sites to provide a consistent level of therapeutic intervention for pediatric patients participating in an ongoing Phase-III, randomized, controlled trial of repeat abobotulinumtoxinA injections for pediatric upper limb spasticity (NCT02106351). Methods: Physical therapists, occupational therapists, and medical doctors worked collaboratively to design an exercise therapy program to be implemented in the home setting. In this article, we describe the development process and the finalized program that is currently being used in the Phase-III trial. Results: The final program is presented as a "toolbox" for therapists, and includes a standardized step-wise process for choosing the most appropriate exercises and functional activities to achieve the agreed treatment goals of each abobotulinumtoxinA injection. The core toolbox includes: a clear protocol for clinicians, information sheets, signature of commitment forms, exercise score charts, and the library of exercises and functional activities that therapists choose from to aid the patient in achieving their treatment goals. Conclusions: Implementation of this home therapy program provides a standardized background of good practice against which to test the efficacy of abobotulinumtoxinA. Preliminary data show that the program is readily accepted by patients and their families.